Komodifikasi Privasi Pada Pasangan Homoseksual Melalui Kanal YouTube - Riyani, Ristia Nurul; Yuhastina, Yuhastina; Trinugraha, Yosafat Hermawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2022)
This paper discusses the commodification practices carried out by homosexual couples through YouTube by making privacy matters a commodity. The study used a netnography method to observe the process of commodification of privacy carried out by homosexual couples and the responses given by netizens. Data was collected through video observations and commentary fields on three YouTube channels, namely: Lucas and Kibo, Rose and Rosie Vlogs, and KaroJerman RagilFred. The results of the study indicate that there is a commodification of content and audiences carried out by homosexual couples through the content in the videos uploaded on their YouTube channel. In addition, there are different responses from netizens for the three YouTube channels. Keyword: homosexual, commodification, youtube